KONSEP STRATEGI PENGEMBANGAN PROGRAM PROFESI KEINSINYURAN PADA JURUSAN PENDIDIKAN TEKNIK MESIN - Basyirun, Basyirun (Jurnal Pendidikan Teknik Mesin, 2005)
According to profession bill, a worker has to be certified. Several efforts could be conducted to make graduate of Mechanical Engineering Education Department accepted as an engineer. They are: reviewing the curriculum, add more 20 Â SKS Â of subjects connected with profession engineer program, and cooperate with PJI to hold profession engineer program. In future these could make a person who can work in both engineering and teaching field.